Islam Disiplin Kerja di Sektor Pendidikan - Nyayu Soraya; Maryamah Maryamah; Nisa Kurnia; Rizqiana Nurfaizah; Putra Pratama, Irja (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
In the world of education, teacher performance is the teacher's ability to fulfill their duties and responsibilities related to student learning outcomes. Factors that can influence teacher performance include the quality of work products, work discipline, initiative and good communication. Islam calls on its followers to be disciplined in various areas of life, including worship, education and work. This research aims to analyze Islamic work discipline in the field of education, looking back at past and future directions. The method used in this research was carried out by reading journals and books related to the research topic. This research uses a qualitative approach. The results of this research show that work discipline, especially in the field of education, has a significant influence on the goals to be achieved.